1999
DOI: 10.1111/j.1151-2916.1999.tb02055.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Aging of Y‐TZP Ceramics

Abstract: The isothermal tetragonal‐to‐monoclinic transformation of a 3Y‐TZP ceramic is investigated from 70° to 130°C in water and in steam by X‐ray diffraction and optical interferometer techniques. Aging kinetics followed by X‐ray diffraction are fitted by the Mehl‐Avrami‐Johnson law, suggesting nucleation and growth to be the key mechanisms for transformation. Optical interferometer observations of highly polished samples effectively reveal a nucleation and growth micromechanism for tetragonal‐to‐monoclinic transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
586
2
38

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 627 publications
(654 citation statements)
references
References 20 publications
(22 reference statements)
28
586
2
38
Order By: Relevance
“…Many studies reported that the major disadvantage of Y-TZP is its reduced stability against low temperature degradation (LTD) [31,[35][36][37][38]. LTD is defined as the spontaneous tetragonal to monoclinic transformation occurring over time at low temperatures, when the transformation is not triggered by the local stress produced at the trip of the advancing crack [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies reported that the major disadvantage of Y-TZP is its reduced stability against low temperature degradation (LTD) [31,[35][36][37][38]. LTD is defined as the spontaneous tetragonal to monoclinic transformation occurring over time at low temperatures, when the transformation is not triggered by the local stress produced at the trip of the advancing crack [2].…”
Section: Discussionmentioning
confidence: 99%
“…Under hydrothermal changes, an undesired phase transformation from tetragonal phase to the weaker monoclinic zirconia can occur on the surface of the monoclinical zirconia FDPs. This is combined with an increase in the surface roughness [37] resulting possibly in high abrasion of the antagonist enamel. Moreover, through the undesired phase transformation as a result of aging, mechanical properties may decrease further [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…For testing the aging behavior after the different surface treatments, the samples were exposed to artificial degradation in autoclave under water vapor at 134 ºC and 2 bar pressure for 30 h. This time was chosen to represent more than the expected life of the application, since it corresponds roughly with 60 years in vivo (Chevalier et al, 1999). After the treatment, the monoclinic phase volume fraction (Vm%) near the surface was measured with XRD by applying the equation of Toraya et al (Toraya et al, 1984) and results were analyzed as in the previous section.…”
Section: Aging Studiesmentioning
confidence: 99%
“…[32] it roughly compares to 60 years in vivo, (note that this equivalence holds only for stress-free materials). X-Ray Diffraction (XRD) patterns were collected before and after the exposure with a Bruker D8 Advance diffractometer using Cu-K radiation and /2 configuration.…”
Section: Characterizationmentioning
confidence: 99%